2012
DOI: 10.1007/s10334-012-0304-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative T 2 * assessment of acute and chronic myocardial ischemia/reperfusion injury in mice

Abstract: ObjectImaging of myocardial infarct composition is essential to assess efficacy of emerging therapeutics. T2* mapping has the potential to image myocardial hemorrhage and fibrosis by virtue of its short T2*. We aimed to quantify T2* in acute and chronic myocardial ischemia/reperfusion (I/R) injury in mice.Materials and methodsI/R-injury was induced in C57BL/6 mice (n = 9). Sham-operated mice (n = 8) served as controls. MRI was performed at baseline, and 1, 7 and 28 days after surgery. MRI at 9.4 T consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…They showed that T2*-weighted images could be used to discriminate between acute and chronic phase of MI, as a reduction of T2* was observed with infarct age, probably because of the presence of iron [3]. Potential interest of such sequence in mouse models of chronic iron overload has also been assessed at field \7 T [110], but still need further validation at HF, as T2* is very sensitive to large scale magnetic field homogeneities, and may be difficult to measure in case of high iron concentration, as signal decay may become rapid [130].…”
Section: T2 and T2* Mappingmentioning
confidence: 97%
“…They showed that T2*-weighted images could be used to discriminate between acute and chronic phase of MI, as a reduction of T2* was observed with infarct age, probably because of the presence of iron [3]. Potential interest of such sequence in mouse models of chronic iron overload has also been assessed at field \7 T [110], but still need further validation at HF, as T2* is very sensitive to large scale magnetic field homogeneities, and may be difficult to measure in case of high iron concentration, as signal decay may become rapid [130].…”
Section: T2 and T2* Mappingmentioning
confidence: 97%
“…This could provide new diagnostic means to a large group of patients excluded from contrast agent injections due to renal insufficiencies. A study employing a mouse myocardial ischemia/reperfusion model has provided first insights into in vivo quantification of T 2 * changes in the mouse myocardium in relation to tissue damage [16]. Local decrease of T 2 * was found in the infarct * Mapping at Ultrahigh Field and HCM patients (right).…”
Section: Discussionmentioning
confidence: 99%
“…T 2 * mapping has been shown to be capable of detecting myocardial ischemia caused by coronary artery stenosis [4], to reveal myocardial perfusion deficits under pharmacological stress [5][6][7][8][9][10], to study endothelial function [11] or to assess breathing maneuver-dependent oxygenation changes in the myocardium [12][13][14][15]. Preclinical studies have also demonstrated the potential of T 2 * mapping to detect structural changes in the infarcted heart muscle and even to distinguish between focal and diffuse fibrosis [16][17][18]. In clinical application T 2 * mapping is the method of choice for quantification of myocardial iron content, an essential parameter for guiding therapy in patients with myocardial iron overload [19][20][21][22][23].…”
Section: T 2 * Sensitized Cardiovascular Magnetic Resonancementioning
confidence: 99%
“…In addition, it has been shown in an in vivo mouse model that the T 2 * value decreases during the initial weeks, when the infarction progresses into the chronic phase . An example of T 2 * mapping in a porcine model of chronic myocardial infarction is shown in Figure (see the Materials and MRI methods section).…”
Section: Endogenous Mri Contrast Myocardial Fibrosismentioning
confidence: 99%